PENGARUH EMPLOYEE ENGAGEMENT DAN WORK LIFE BALANCE TERHADAP KINERJA KARYAWAN MELALUI KEPUASAN KERJA - Jihan Ayu Pratiwi; Fandi Fatoni (Jurnal Ilmu Manajemen, 2023)
The company is a business entity with specific goals for its business activities. It requires employees as the driving force of its operating system. This study examines and analyzes the effect of employee engagement and work-life balance on employee performance through job satisfaction. This research is a causality study with a quantitative approach. This study used a probability sampling technique, i.e., proportionate stratified random sampling, with 87 respondents. The data were analyzed using the Structural Equation Model (SEM) with the Partial Least Squared (PLS) analysis method and with the help of smartPLS 3.0 software. The results explain that Employee Engagement positively and significantly affects employee performance. Work-life balance has a positive and significant effect on employee performance. Employee engagement has a positive and significant effect on job satisfaction. Work-life balance has a positive and significant effect on job satisfaction. Job satisfaction has no significant effect on employee performance. Job satisfaction cannot mediate the effect of employee engagement on employee performance. Job satisfaction cannot mediate the effect of work-life balance on employee performance. Companies can pay more attention to employee performance by improving the quality of their employees through employee engagement and work-life balance factors so that job satisfaction can be fulfilled and employee performance can continue to increase.